Communication on COVID-19 Vaccination in Indonesia and the Truth of the Digital Society - Arsyad, Annisa Wahyuni; Boer, Kheyene Molekandella; Noor, Muhammad (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
COVID-19 vaccination during the pandemic appears and is considered an innovation or new thing that must be quickly implemented to minimize epidemic transmission. As a country affected by COVID-19, Indonesia has also started distributing vaccines to various parties. The distribution process encountered various challenges. One of them is the truth or public trust in the government regarding handling the COVID-19 outbreak, which affects people's decisions not to or to carry out vaccines. This paper uses a non-interactive qualitative method by collecting various information about COVID-19 vaccination from a communication perspective. The theory used is the diffusion of innovation to see how the people of Indonesia can accept vaccines amid many people's doubts about the government. Truth is an important concept that determines the success of the COVID-19 vaccine. However, there is much public apathy towards the government's work rhythm; on the other hand, the government continues to intensively socialize various ways related to the benefits of vaccines, safety, easy ways to get vaccines and other benefits. The government can achieve at least 70% of the Indonesian sub-population vaccination target by gaining trust.